2013
DOI: 10.1177/0020764013491738
|View full text |Cite
|
Sign up to set email alerts
|

Self-stigma, quality of life and schizophrenia: An outpatient clinic survey in Nigeria

Abstract: This study revealed that self-stigma was common among subjects with schizophrenia. It is associated with poor treatment outcome, highlighting the need to incorporate stigma intervention strategies into mental health care delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
45
2
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(60 citation statements)
references
References 48 publications
6
45
2
7
Order By: Relevance
“…Most participants in our study reported experiencing various forms of discrimination, labelling, insult and feelings of low self-worth because of their diagnosis of schizophrenia. These results are similar to a study from Nigeria that found a high level of self-stigma among outpatients with schizophrenia [66]. The matter of self-stigma also has important implications for health service managers.…”
Section: Stigma and Discrimination Compounded By Socio-cultural Beliefssupporting
confidence: 87%
“…Most participants in our study reported experiencing various forms of discrimination, labelling, insult and feelings of low self-worth because of their diagnosis of schizophrenia. These results are similar to a study from Nigeria that found a high level of self-stigma among outpatients with schizophrenia [66]. The matter of self-stigma also has important implications for health service managers.…”
Section: Stigma and Discrimination Compounded By Socio-cultural Beliefssupporting
confidence: 87%
“…High perceptions of self-stigma in individuals with mental disorders have been reported across cultures. The few reports from Africa are not dissimilar to those from elsewhere [38, 44]…”
Section: Discussionmentioning
confidence: 99%
“…A multinational review of its validation studies reported good reliability and validity, including the Yoruba and Swahili versions [36], A Cronbach’s alpha of 0.90 for internal reliability and a test-retest reliability coefficient of 0.92 have been demonstrated for the tool [25]. It has also been used in several studies in Africa [37, 38) with a Cronbach’s apha of 0.84 and a test retest reliability coefficient of 0.86 in a Nigerian population [37]. Each item on the scale is scored from 1 to 4 likert scale.…”
Section: Methodsmentioning
confidence: 99%
“…Stigma was assessed by three well-validated instruments (ISMIS, EMIC and P-scales), used in earlier studies on stigma with schizophrenia[2930313233] and including in India for stigma with mental as well as physical illnesses. [34] With some overlap, these scales evaluate different aspects of stigma experienced by patients with schizophrenia.…”
Section: Discussionmentioning
confidence: 99%